Investment Grade Energy Audit: A Financial Tool for the Cost-effective Renovation of Residential Buildings. (May 2015) - Bonacina, Carlo F.; Masera, Gabriele; Pavan, Alberto
Abstract: The renovation of the existing building stock is a top priority for the European Union. In order to reach the ambitious goal of decarbonization by 2050, new financial instruments, incentives or grants and loans to support energy efficiency should be implemented, especially for public bodies. The proposed method aims to be a tool to stimulate cost-effective deep renovations. The results of its application to a multi-owner building show the benefits of using Energy Service Companies and Energy Performance Contractingto finance renovations and implement plans to maintain or improve energy efficiency in the long term.